A comparative analysis of barn and platform as storage structures for yam tuber in Ibadan, Nigeria (2010)
An experimental study was undertaken to evaluate and compare the performances of a local barn and a platform, as storage structures for yam tubers (Dioscorea rotundata poir.) The criteria used for evaluation and comparison were the degree of weight loss during storage, tuber sprouting and rotting of yam tubers during a 17 week storage duration between March and June 2008. Measurements of temperatures and relative humidity in the storage environment were taken thrice daily during the period. Weight loss in each tuber was measured weekly while sprouts were removed from tubers fortnightly. Results show that the average temperature and relative humidity on the platform were 30.4°C and 57.3% respectively while for the barn, they were 26.5°C and 55.5% respectively. The average weight loss in tubers in the barn during the duration was 32.8% while for tubers on the platform, it was 30.3%. Yam tubers on the platform recorded 5.4% sprouting while those in the barn had 4.9% sprouting. Palm leaves cover for yam tubers on the platform protected the tubers from excessive heat and moisture loss. Rotting was observed in 10% of the tubers stored in the barn but was completely absent from those stored on the platform.